INFLUENCE OF EPICHLOROHYDRIN ON THE STATE OF THE DUODENAL MUCOSA CRYPTS IN RATS AND CORRECTION OF THE CONSEQUENCES CAUSED BY THIS EFFECT - Mirzebasov, M.A.; Smirnov, A.S.; Smirnov, S.N. (World of Medicine and Biology, 2019)
The state of a modern person health is largely dependent on the influence of chemicals that are anthropogenic pollutants of the environment. Epichlorohydrin (ECH) is one such chemical. The patterns of influence of ECH on the duodenum are not well understood. The purpose of the work was to study changes in the state of the crypts of the duodenal mucosa in rats under ECH influence. An experimental study was performed on male white rats. The depth of the crypts and the number of G-endocrinocytes in one crypt of the duodenal mucosa were estimated using a microscope of the MS 100 series of Micros (Austria). Duodenal mucosa morphofunctional organization in rats changed after the long-term introduction of ECH. The depth of the crypt and the number of G-endocrinocytes in one crypt were reducing. The use of an Echinacea purpurea extract, as well as the use of thiotriazoline during ECH inhalations reduces the severity and duration of the decrease in the depth of the crypts and prevented the development of a decrease in the number of G-endocrinocytes in one crypt that were caused by ECH. The negative effects of ECH were corrected more effective by thiotriazoline than by EP extract.